2013
DOI: 10.1111/1365-2656.12036
|View full text |Cite
|
Sign up to set email alerts
|

Colony life history and lifetime reproductive success of red harvester ant colonies

Abstract: Summary1. We estimate colony reproductive success, in numbers of offspring colonies arising from a colony's daughter queens, of colonies of the red harvester ant, Pogonomyrmex barbatus. 2. A measure of lifetime reproductive success is essential to understand the relation of ecological factors, phenotype and fitness in a natural population. This was possible for the first time in a natural population of ant colonies using data from long-term study of a population of colonies in south-eastern Arizona, for which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 94 publications
(152 reference statements)
3
36
1
Order By: Relevance
“…The results of this experiment add to those of earlier studies of ants that found that colony fitness can be inferred by the mass of adult reproductives and colony size (Gordon , Deslippe and Savolainen , Wagner and Gordon , but see Ingram et al. ).…”
Section: Discussionsupporting
confidence: 80%
“…The results of this experiment add to those of earlier studies of ants that found that colony fitness can be inferred by the mass of adult reproductives and colony size (Gordon , Deslippe and Savolainen , Wagner and Gordon , but see Ingram et al. ).…”
Section: Discussionsupporting
confidence: 80%
“…Despite the analogy, comprehensive studies of colony level life-histories remain few (but see e.g., Cole, 2009;Ingram et al, 2013), and the life-span reproduction trade-offs have not been intensely studied at the colony level. The superorganismal perspective is further justified by the observation that at the lower level of individuals within colonies social insects break the tradeoffs that apply to solitary organisms.…”
Section: Life History Trade-offsmentioning
confidence: 99%
“…Morepronounced physiological variation among colonies would probably be detected if biogenic amine levels were quantified at the brain-region scale, or if gene expression patterns were quantified at the single-cell scale 51 . It would be interesting to examine the association between variation in the traits measured here and colony fitness, and relatedness among colonies, as in previous work 9,52 . However, we do not have fitness estimates for this set of colonies.…”
Section: Discussionmentioning
confidence: 96%